2022
DOI: 10.1021/acsmaterialslett.2c00322
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Interfacial Adjustment of Magnetoresistance in Organic Spin Valves Using Isoindigo-Based Polymers

Abstract: The organic interlayer is a crucial part in organic spin valves (OSVs), and its molecular structure has an important effect on the device performance. In this work, we utilized conjugated polymers based on isoindigo derivatives (PIID-TVTCN, PAIID-TVTCN, and PFIID-TVTCN) to fabricate OSVs and studied the dependence of the performance on the polymer structure. Positive magnetoresistance (MR) was obtained in OSVs with 40 nm polymeric thin films. Under the same conditions, the introduction of a pyridine nitrogen i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Such incongruence between the MR curves and magnetization states has also been reported in other studies. 1,7,9,14 For example, in Alq 3 -based MR devices, the top electrode (Co) and bottom electrode (LSMO) showed coercivities of 150 and 30 Oe, respectively, which are not in good agreement with the values 170 and 70 Oe, respectively, estimated from the observed MR effect. 1 In another study, the MR effect was observed in Ni/benzene-1,4-dithiol (BDT)/Ni single molecular junctions using mechanically controllable break junction (BJ) method.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Such incongruence between the MR curves and magnetization states has also been reported in other studies. 1,7,9,14 For example, in Alq 3 -based MR devices, the top electrode (Co) and bottom electrode (LSMO) showed coercivities of 150 and 30 Oe, respectively, which are not in good agreement with the values 170 and 70 Oe, respectively, estimated from the observed MR effect. 1 In another study, the MR effect was observed in Ni/benzene-1,4-dithiol (BDT)/Ni single molecular junctions using mechanically controllable break junction (BJ) method.…”
Section: Resultsmentioning
confidence: 79%
“…Typical molecular spintronic devices are organic spin valves (OSVs) which consist of organic molecules sandwiched between two magnetic layers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] These types of devices show a large magnetoresistance (MR) effect. The resistance of such devices changes according to the conguration of the magnetization vectors in both magnetic layers adjacent to the molecular layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…electrode and the MR curve of OSV device could be assigned to the interfical hybrid states between Co electrode and the organic active layer, which affected the coercive behavior of Co electrode. [26,30] It was noteworthy that the MÀ H curve depicted in Figure S17 demonstrated no evidence of FM behavior for the reactivated COF powder. Therefore, during the scanning of external magnetic field from + 2000 to À 2000 Oe, the resistance of the OSVs was initially switched at a low magnetic field corresponding to the coercive field of LSMO, and then converted to a large resistivity state under high fields, and vice versa (Figure 4c).…”
Section: Forschungsartikelmentioning
confidence: 98%
“…82 Likewise, the positive MR values were also obtained in OSVs based on P88–P90 . 142 Yu and co-workers synthesized P91–P94 by introducing a cyano group on the double bonds of TVT, and investigated the structure–property relationships in OFETs and OSVs. 143 The results suggested that the introduction of pyridine nitrogen atoms enhanced the electron mobilities of OFETs and MR values of OSVs, whereas the extension of alkyl chain branching points lowered the MR values.…”
Section: Semiconducting Polymers Based On Diarylethylene Unitsmentioning
confidence: 99%